Analisis Kinerja Keuangan Pada PT. Gudang Garam TBK Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2020-2024 - Febriani Nur Rahman; Meiman Kristian Putra Gulo; Echa Salsabilla; Fitri Yani Panggabean (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to assess the financial performance of PT Gudang Garam Tbk during the period 2020 to 2024 through analysis of liquidity, solvency, and profitability ratios. The approach used is descriptive quantitative based on annual financial statement data. The analysis results show that the liquidity ratio is unstable due to an increase in current debt that is not proportional to current assets. Solvency ratios show a positive trend supported by an increase in total assets. However, profitability ratios such as ROA, ROE, and NPM have decreased, which indicates low efficiency in asset and capital utilization. In general, the company has not met industry standards and requires improvements in financial management in order to improve performance sustainably.